Optimizing pipeline systems with surge tanks using a dimensionless transient model - Kim, Sanghyun (Journal of hydroinformatics, 2024)
The design factor of surge tank installation is a practical issue in the management of pressurized pipeline systems. To determine the general criteria for surge tank design in pipeline systems, dimensionless governing equations for unsteady flow and their solutions were developed for two widely used pipeline systems equipped with surge tanks. One is the reservoir pipeline surge tank valve and the other is the pipeline system with a pumping station and check valve protected by the surge tank. Two distinct time-domain responses, point- and line-integrated pressure, can be used as objective functions to optimize the surge tank area. The developed formulations were integrated into a metaheuristic engine, particle swarm optimization, to explore a general solution for a wide range of dimensionless resistances that comprehensively address various flow features into one dimensionless parameter. Depending on the dimensionless location of the surge tank, the optimum dimensionless surge tank areas were delineated for a range of dimensionless resistances for the two pipeline systems with and without a pumping station protected by a surge tank.